Entrepreneurship and Security Solution toward Millennium Development Goals: Assessing the Effect of Entrepreneurial Education on Secondary School Students’ Ability to Address Economic Security Challenges in Anambra State, Nigeria - Uchenna Favour Muogbo; Uju Susan Muogbo; Chinwe Juliana Enemuo (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: This study examined the effect of entrepreneurial education on secondary school students' ability to address economic security challenges in Anambra State, Nigeria. Objective: The study aimed to investigate how entrepreneurial education influences students' critical thinking, innovation, and problem-solving skills, as well as its potential to enhance their ability to cope with economic instability. Method: Using a descriptive survey design, data were collected from all 263 principals across six educational zones. No sampling was done as the population was manageable. A self-structured 30-item questionnaire titled